Niat Penggunaan Kondom pada Komunitas Waria di Kota Ternate - Eda, Nur (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2012)
Pada tahun 2008 sampai dengan 2009, di Kota Ternate terdapat 3 orang waria positif HIV/AIDS dan 7 lainnya memiliki gejala – gejala yang diduga gejala HIV/AIDS, dan pada tahun2011(November) ditemukan 2 orang waria meninggal dengan HIV/AIDS. Penelitian ini bertujuanuntuk mengetahui faktor-faktor yang mempengaruhi niat penggunaan kondom pada komunitaswaria di kota Ternate. Penelitian ini menggunakan metode kuantitatif dengan rancanganxxplanatory research dengan pendekatan cross sectional. Besar sampel sebanyak 135 orangwaria. Analisa data dilakukan secara univariat, bivariat dengan chi-square dan multivariatdengan regresi logistik. Hasil penelitian menunjukkan sebagian besar responden (55.6%) berniatmenggunakan kondom saat melakukan hubungan seks. Faktor yang paling berpengaruhterhadap niat penggunaan kondom pada komunitas waria di kota Ternate adalah adanyapersepsi kerentanan terhadap penularan IMS dan HIV/AIDS. Variabel yang berhubunganterhadap niat penggunaan kondom adalah persepsi kerentanan terjangkit IMS dan HIV/AIDSdan persepsi kemampuan diri. Diharapkan kepada Dinas Kesehatan Kota Ternate agarmeningkatkan pengetahuan masyarakat khususnya waria dengan cara meningkatkan sosialisasitentang pengertian, penularan dan pencegahan HIV/AIDS dalam program pencegahanpenularan IMS dan HIV/AIDS.Kata Kunci : niat, penggunaan pondom, waria . The Factors Influencing Intention Of Condom Use At Transvestite Community In TernateCity; People with HIV / AIDS in Ternate city tend to increase from the year 2007 are amounted3 people, in 2008 are five people, in 2009 are 8 people, in 2010 are 10 people, and in 2011(November) are 9 people. In the year of 2008 to 2009 based on information from NGOs Kiarahatransvestites there are 10 people died, 3 people positive HIV / AIDS and other 7 had symptomsof suspected the symptoms of HIV / AIDS, and in 2011 discovered two transsexual people diedwith HIV / AIDS. Transvestites are high risk group that are vulnerable of sexually transmittedinfections because they have number of sexual partners more than other group . This aim ofstudy to determine the factors that influence of intention of condom use at transvestite communityin ternate city.This study used quantitative methods with explanatory research and cross sectionalapproach. The sample size is 135 peoples. Data analysis used univariat analysis, bivariate analysiswith cross tabulation and chi square and Multivariate logistic Regression. The results showedmost respondents (55,6%) intend to use condom during sexual intercourse. The factors thatmost influence of intention to use condom at transvestite community in Ternate City is theperception of vulnerability of sexually transmitted infections and HIV/AIDS, Variable that relatedto the intention of condom use is the perception of vulnerability contracting sexually transmittedinfections and HIV/AIDS, and ability of self perception. To increase knowledge of community about transmission and prevention of HIV / AIDS, Ternate’s health department must givesocialization and counselling to communities especially transvestites about condom use andsexually transmitted infection and HIV/AIDSKeywords: intention,condom use, ttansvestite.